The impact of the symposia of the Institute for Theological Research (UNISA): 1977–1992 - Christina Landman (Verbum et Ecclesia)
Established in 1975 at the University of South Africa (UNISA), the Research Institute for Theology and Religion (RITR), formerly known as the Institute for Theological Research (ITR), will commemorate its 50th anniversary in 2025. Among the ITR’s key scholarly contributions and outputs were the annual symposia, of which 16 were held consecutively between 1977 and 1992. Prof Willem Vorster was the Director of the ITS from its establishment in 1975 to his death in 1993. It was under his leadership that these symposia were held.